2021
DOI: 10.1002/dvg.23417
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion GPCR Adgrg6 (Gpr126): Insights from the zebrafish model

Abstract: Summary Adhesion GPCRs are important regulators of conserved developmental processes and represent an untapped pool of potential targets for drug discovery. The adhesion GPCR Adgrg6 (Gpr126) has critical developmental roles in Schwann cell maturation and inner ear morphogenesis in the zebrafish embryo. Mutations in the human ADGRG6 gene can result in severe deficits in peripheral myelination, and variants have been associated with many other disease conditions. Here, we review work on the zebrafish Adgrg6 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 107 publications
(207 reference statements)
0
10
0
Order By: Relevance
“…The Gpr126-deficient mice show an embryonic lethal phenotype mainly due to cardiac abnormality [103]. In addition, Gpr126 deficiency also leads to multiple defects in peripheral nerves [104], inner ear (in zebrafish) [105], placental development [106], and lack of myelination in the peripheral nervous system (PNS) [107]. More recent studies in cell typespecific Gpr126 knock out animals further indicated a role for GPR126 in the regulation of body length and bone mass as well as the maintenance of spinal alignment [108,109].…”
Section: Adgrg6/gpr126mentioning
confidence: 99%
“…The Gpr126-deficient mice show an embryonic lethal phenotype mainly due to cardiac abnormality [103]. In addition, Gpr126 deficiency also leads to multiple defects in peripheral nerves [104], inner ear (in zebrafish) [105], placental development [106], and lack of myelination in the peripheral nervous system (PNS) [107]. More recent studies in cell typespecific Gpr126 knock out animals further indicated a role for GPR126 in the regulation of body length and bone mass as well as the maintenance of spinal alignment [108,109].…”
Section: Adgrg6/gpr126mentioning
confidence: 99%
“…Additional activation can be achieved through the receptor’s N-terminal ligands collagen IV ( Paavola et al, 2014 ), prion protein PrP C ( Küffer et al, 2016 ), and laminin 211 ( Petersen et al, 2015 ). Yet, none of these agonists is specific for GPR126, and ECM proteins lack characteristics of a classic receptor agonist as they are long-lived, stable molecules with essentially no diffusivity ( Bassilana et al, 2019 ; Baxendale et al, 2021 ). Thus, it is unclear how the interaction between aGPCR and the ECM can be interpreted as a specific signal to modulate receptor activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GPR126 has been reported to have critical roles in the normal development of diverse organs and tissues, including Schwann cells and peripheral nervous system myelination, bone, inner ear, and placenta (Baxendale et al, 2021). Of note, human GPR126 mutations are linked to several nonneurological diseases, such as adolescent idiopathic scoliosis (Kou et al, 2013), arthrogryposis multiplex congenital (Ravenscroft et al, 2015), and carcinogenesis (An et al, 2022).…”
Section: Introductionmentioning
confidence: 99%